Impact of natural products on Acyrthosiphon pisum density on Pisum sativum L. and forage quality - Nikolova, Ivelina (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
A field trial was conducted at the Institute of Forage Crops (Pleven, Bulgaria) from 2015 to 2017. It studied the effects of natural products on Acyrthosiphon pisum density, as well as changes in the chemical composition, content of plant fibre components and enzyme degradability in forage pea. Treatments with the natural insecticides Madex and Agricolle, applied alone or in combination with the organic fertilizers Lithovit and Nagro were performed twice - at the beginning of the flowering stage and one week later. The fertilizers used in the trial are environmentally safe and approved for use in organic production. The synthetic products Kristalon, a foliar fertilizer, and Proteus 110 OD, an insecticide, were used for comparison. The application of natural products, either alone and in combination, resulted in a reduction in pea aphid density. Applying Agricolle with Nagro, followed by Lithovit with Agricolle, led to the highest aphid number decrease (70.0 and 51.1%, respectively). An optimal combination of decrease in the content of plant cell wall fibre components, cellulose and lignification degree with a significant increase in forage in vitro enzyme digestibility was established after applying Agricolle with Lithovit and Agricole with Nagro. Digestibility reached 71.8 and 69.8%, respectively, an increase of 8.2-5.2%, while ADF, cellulose and lignification degree decreased from 7.1 and 7.7%, 8.0 and 23.4%, amd 10.5 and 6.8% after applying Agricolle with Lithovit and Agricole with Nagro, respectively. In comparison, the synthetic products Kristalon and Kristalon with Proteus increased forage quality, but to a relatively lesser extent. A stronger linear relationship was found between aphid density and dry matter digestibility, compared to the content of neutral detergent fibres. Pea forage with low content of plant cell wall fibre components, cellulose and lignification degree, high protein content, and digestibility after treatment with the natural product Agricolle, and its combinations with Lithovit and Nagro, make it a very good complement to other forages in dairy cow rations.